O controle jurisdicional de políticas públicas de saneamento básico e seus limites em casos de omissões administrativas - Zilles, Fabiana (Universidade do Vale do Rio dos Sinos, 2015)
This dissertation investigates the possibility of judicial review of public policies sanitation in cases of omissivas conduct of public administration in the Brazilian Constitutional System and its limits. The legal basis of this control derives from the constitutionalization of the right to an ecologically balanced environment in the Brazilian Constitution and that it granted the Brazilian judges the duty of controlling the constitutionality of laws and administrative acts, as well as a fundamental right enshrined the fact that can not be excluded from review by the Judiciary injury or threat to a right. First, the research studies the interdisciplinary concept of public policy and the objections to judicial review in cases of administrative omissions, especially in view of the principle of separation of powers and the concept of administrative discretion. After analyzes the implications of the recognition by the Brazilian Federal Constitution of the fundamental right to a balanced environment and the healthy state of life and its principle of compulsory state intervention, and the inextricable interrelationship of this fundamental right with the right to sanitation, expressly recognized by United Nations also as a fundamental right. Further, the study verifies the question of the principle of reserve for contingencies and existential minimum in terms of sanitation and seeks ways to establish jurisdictional control of such public policies and their limits, in the light of constitutional principles affecting the interpretation and analyzes benchmarks of breaches of the right to basic sanitation in accordance with the principles of the law of national guidelines for basic sanitation.
Keywords: Meio ambiente equilibrado; Saneamento básico; Políticas públicas; Controle jurisdicional; Limites; Balanced environment; Sanitation; Public policy; Judicial review; Limits; ACCNPQ::Ciências Sociais Aplicadas::Direito